POLITIK dan TASAWUF : Mengeyimbangkan Antara Partisipasi Sosial dan Kesalehan Individual - Syahuri Arsyi; Mohammad Mahmudi; Moh Irwansyah Thoyyib; Riyan Hidayatullah (VIRTUOUS JOURNAL, 2024)
The subjects in this paper are politics and Sufism, both of which are very paradoxical themes. Politics in practice is more inclined to the meaning of violence, manipulation and agitation, as well as to something that is materialistic and secular. On the contrary, Sufism means purification of the soul, clean, holy, polite, peaceful, and far from manipulation, and makes a person better without having to leave social life, both in social, political, economic and so on. These two different terminologies will be connected in the context of the application of power politics. In the Islamic world Sufism is one way to help the process of political activity with the aim of creating a just, peaceful and prosperous society. A sufi must take a role in the social sphere including in political upheavals. It is from this that the application of the teachings of Sufism to political activity in its aspect becomes very important.